Analysis of the DPRK's Nuclear Weapons Capabilities by Estimating Its Highly Enriched Uranium Stockpile and Natural Uranium Reserves. Issue 2 (2nd September 2019) - Kurbanbekov, Sherzod R.; Min Woo, Seung; Chirayath, Sunil S.
Abstract: There is a shortage of reliable information on the highly enriched uranium (HEU) stockpile, production capabilities, and natural uranium reserves of the Democratic People's Republic of Korea (DPRK or North Korea). It is, however, possible to estimate DPRK's nuclear material reserves using the data in the open literature and considering various scenarios. Based on our literature survey and analysis we are projecting DPRK's natural uranium reserves and their production capabilities of weapons-grade HEU. We also report the uncertainties associated with DPRK's uranium enrichment capabilities due to the differences in estimates provided in the literature. Our analysis shows that given the range of the estimates of DPRK's natural uranium ore reserves, its nuclear weapons program is unlikely to be constrained by uranium resources, provided they have the required mining and milling capacities.